Fundamentals of physics : - Halliday, David (John Wiley & Sons, Inc., 2001)
The principle goal of this book is to provide instructors with a tool by wich they can teach students how to effectively read scientific material and successfully reason through scientific questions. To sharpen this tool, this enhanced version of the sixth edition of Fundamentals of Physics contains over 1000 new, high-quality problems that require thought and reasoning rather than simplistic plugging of data into formulas.